Leadership Dalam Bingkai Islam: Suatu Pemikiran Kolaboratif-Elaboratif Pada Perspektif Gender Dalam Menguak Kepemimpinan Perempuan: Leadership in the Islamic Framework: A Collaborative-Elaborative Approach to Gender Perspectives in Uncovering Women's Leadership - Titiek Rohana Hidayati (An-Nisa’ Journal of Gender Studies, 2009)
The figure of a leader is often the subject of intense scrutiny from all sides, whether in terms of behavior, character, capabilities, or abilities. As such, these factors are often used to justify whether or not someone is capable of holding the role of leader. These are urgent considerations in determining a leader. In fact, if we look at historical data, the issue of leadership was the first problem that was disputed after the death of the Prophet SAW. At the very least, we do not find Arabic terms that explicitly mean state or government (dawlah and hukumah) mentioned explicitly in the Qur'an. In its development, some modern literature later reached agreements on matters that fall within the scope of leadership. Figur seorang pemimpin, acapkali menjadi sorotan tajam dari semua pihak, baik dari sisi perilaku, karakter, kapabilitas, dan kemampuannya. Sehingga, seringkali faktorfaktor tersebut seringkali dijustifikasi sebagai penanda mampu dan tidaknya seseorang memegang peran sebagai pemimpin. menjadi sisi-sisi urgen untuk menentukan sosok pemimpin. Bahkan, jika mengaca pada data historis, masalah pemimpin /kepemimpiann inilah yang menjadikan problem pertama yang diperselisihkan pasca wafatnya Nabi SAW. Paling tidak, kita tidak mendapatkan terma bahasa Arab yang secara eksplisit bermakna negara atau pemerintahan (dawlah dan hukumah) disebut-sebut oleh al-Qur`an dengan pasti. Dalam perkembangannya, di beberapa literatur modern kemudian didapatkankesepakatan-kesepakatan mengenai hal-hal yang menjadi wilayah kerja pemimpinan itu.